Perturbing nuclear glycosylation in the mouse preimplantation embryo slows down embryonic development - Sara Formichetti; Joana B. Serrano; Urvashi Chitnavis; Agnieszka Sadowska; Na Liu; Ana Boskovic; Matthieu Boulard (Proceedings of the National Academy of Sciences, 2025)
The main form of intracellular protein glycosylation (O-GlcNAc) is reversible and has been mapped on thousands of cytoplasmic and nuclear proteins, including RNA polymerase II, transcription factors, and chromatin modifiers. The O-GlcNAc modification is catalyzed by a single enzyme known as O-GlcNAc Transferase, that is required for mammalian early development. Yet, neither the regulatory function of protein O-GlcNAcylation in the embryo nor the embryonic O-GlcNAc proteome have been documented. Here, we devised a strategy to enzymatically remove O-GlcNAc from preimplantation embryonic nuclei, where this modification accumulates coincidently with embryonic genome activation (EGA). Unexpectedly, the depletion of nuclear O-GlcNAc to undetectable levels has no impact on EGA, but dampens the transcriptional upregulation of the translational machinery, and triggers a spindle checkpoint response. These molecular alterations were phenotypically associated with a developmental delay starting from early cleavage stages and persisting after embryo implantation, establishing a link between nuclear glycosylation and the pace of embryonic development.